UTILIZATION OF SAMBUNG NYAWA LEAF EXTRACTS Gynura procumbens (Lour) Merr. FOR TREATMENT OF Vibrio alginolyticus IN TIGER GROUPER (Epinephelus fuscoguttatus Forsskal, 1775) - Novi Santika; Wardiyanto Wardiyanto; Esti Harpeni (Berkala Perikanan Terubuk, 2019)
Tiger Grouper is one of the sea water fish commodities that is quite popular with the community and has a high economic value. The problem faced by farmers is the attack of Vibriosis, one of which is caused by the Vibrio alginolyticus bacteria. The use of synthetic antibiotics has been widely used but has many adverse effects, so it needs new alternatives for the treatment of Vibriosis disease. One of them is by using the extract of lifelong leaf extract. Life-sustaining plants (Gynura procumbens) contain secondary metabolites such as flavonoids, tannins, and antibacterial saponins. This study aims to determine the best dosage of lifelong leaf extract for the treatment of Vibriosis disease in tiger grouper. The study was conducted in two stages, namely in vitro and in vivo. Before the fish were treated with feed that had been given a sambung deca leaf extract, the fish were challenged using Vibrio alginolyticus with a density of 108 CFU / mL as much as 0.1 mL / head and then fed with treatment and maintained for 21 days. The results of the in vitro study showed that the life of sambung leaf extract at a dose of 700 ppm had a broad inhibitory effect on V. alginolyticus, which amounted to 10.47 mm compared to other treatments. Whereas when continued for in vivo testing, a dose of 350 ppm in general has been applied for the treatment of attacks of Vibrio alginolyticus in tiger grouper.